Flexible and thermal conductive poly (vinylidene fluoride) composites with silver decorated hexagonal boron nitride/silicon carbide hybrid filler. Issue 6 (21st April 2022) - Hu, Lanlan; Yang, Wulin; Zhu, Jiajun; Fu, Licai; Li, Deyi; Zhou, Lingping
Abstract: In this work, a novel thermal conductive and electrical insulation composite paper fabricated through doctor‐blading followed by hot‐pressing was reported. Specifically, by loading silver nanoparticles (AgNPs) on the surface of boron nitride nanosheets (BNNS) and silicon carbide wires (SiCw), the BNNS and SiCw were bridged through the sintered AgNPs to form a heat conduction path. The results indicate that the prepared composite paper not only enhances the thermal conductivity to 47 W m −1  k −1 but also possesses good mechanical properties and high electrical insulation. The optimizations can be attributed to the efficient BNNS/Ag/SiCw networks within the paper and strong interfacial combination through sintered AgNPs. Furthermore, the distribution and size of the AgNPs also affect the properties of the composites. This work provides a promising strategy to improve thermal conductivity of the composites by constructing efficient thermal conductive pathways, which are suitable for large‐scale preparation and have potential to be widely used in the field of electronic packaging. Abstract :